Pemanfaatan Produk UMKM Pondok Pesantren Darul Hikmah Dalam Meningkatkan Kesejahteraan Ekonomi Masyarakat Di Desa Bah Joga Kecamatan Jawa Maraja Bah Jambi Kabupaten Simalungun - Rachma Ayu, Melati; Madya, Efi Brata (Ganaya : Jurnal Ilmu Sosial dan Humaniora, 2025)
Before the existence of UMKM products of Darul Hikmah Islamic Boarding School, there were many unemployed in Bah Joga Village, and the income of the local community only came from livestock activities, palm weaving such as gedek which was then bought and sold, and agricultural activities, but many people became farm laborers in fields that were not theirs. This caused the community not to get maximum income and were far from welfare. The purpose of this study was to examine the use of UMKM products at Darul Hikmah Islamic Boarding School in improving the economic welfare of the community in Bah Joga Village, Jawa Maraja Bah District, Jambi, Simalungun Regency. The research method used was a qualitative approach with data collection techniques through observation, interviews, and documentation studies. The results of the study showed that UMKM products of the Islamic boarding school, such as processed foods, handicrafts, and agricultural products, made a significant contribution to encouraging the economic growth of the surrounding community. Through community-based marketing and partnership networks, these products were able to increase the income of students, alumni, and the local community. Collaboration between Islamic boarding schools and the community in developing MSMEs is the creation of a mutually beneficial relationship (mutualistic symbiosis) in building economic independence based on Islamic values. In addition, the entrepreneurship training program held by Islamic boarding schools also equips the community with the skills needed to become entrepreneurs independently. Thus, the utilization of MSME products from Darul Hikmah Islamic Boarding School has been proven to contribute to improving the economic welfare of village communities in a sustainable manner. Thus, Islamic boarding schools not only function as educational institutions, but also as the main drivers of the economy that have a positive impact on the welfare of society as a whole.